HUBUNGAN ANTARA SELF EFFICACY, DISIPLIN, TANGGUNG JAWAB, DAN MINAT BELAJAR DENGAN HASIL BELAJAR MATEMATIKA - Sugeng, Sugeng; Marzuki, Marzuki; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to describe the relationship between: self efficacy with learning outcomes, discipline with learning outcomes, responsibility with learning outcomes, interest in learning with learning outcomes, self efficacy, discipline, responsibility and interest in learning joint learning outcomes, as well as, and major responsibilities contributing to success, discipline, responsibility and interest in learning towards the results of mathematics learning in fourth grade students of 28 Pontianak Elementary School. This study uses descriptVe methods using quantitatVe. This type of research is correlational. This study is a population research with a population of 66 students. Data collection is done using a questionnaire instrument. Data analysis techniques were carried out by descriptVe statistical analysis, while to determine the relationship between variable variables namely self efficacy, discipline, responsibility and interest in learning with mathematics learning outcomes were used through simple calculations and multiple conversions. The results showed that there was a positVe and significant relationship between: self efficacy with learning outcomes, discipline with learning outcomes, responsibility with learning outcomes, interest in learning with learning outcomes, self efficacy, discipline, responsibility answer answer and interest in learning together with learning outcomes with the results of mathematics learning in fourth grade students of 28 Pontianak Elementary School.Keywords : Discipline, Interest, Mathematics Learning Outcomes, Responsibility, Self Efficacy